The Effectiveness of High Fidelity Simulation Towards Knowledge and Skills in Health Education: Literature Review - Chiyar Edison S. (Universitas Faletehan, 2018)
High Fidelity Simulation (HFS) has been recently deemed an effective approach to resemble the real clinical situation so that the improvement of knowledge and skill of student are much more significant. However, there has been much debate in recent times whether this method is much more effective than conventional simulation. This literature review aimed to present the evidence supporting of the effectiveness of HFS especially in enhancing knowledge and skill of health care student. Search terms including “high fidelity simulation”, “knowledge” and “skill” were processed into CINAHL, PubMed and Bristish Nursing Index. All papers that published after 2005 and primary research were included. There were totally 9 papers included in this review, as a result of back chaining method involved in searching strategy. This review suggests that HFS is able to improve skill and knowledge of student effectively.